Proportions of four distinct classes of sensory neurons are retained even when axon regeneration is enhanced following peripheral nerve injury - Khan, Samia; Carrasco, Dario I.; Isaacson, Robin; English, Arthur W. (Frontiers in Neuroanatomy, 2023)
Introduction Recovery from peripheral nerve injuries is poor because axon regeneration is slow and inefficient. Experimental therapies that increase signaling of neuronal brain-derived neurotrophic factor (BDNF) through its TrkB receptor or through its downstream effectors enhance axon regeneration, increasing the number of motor and sensory neurons whose axons successfully regenerate and reinnervate muscle targets. The goal of this study was to compare the proportions of four different classes of sensory (dorsal root ganglion, DRG) neurons that successfully reinnervate two different muscle targets in control mice and mice treated pharmacologically to enhance axon regeneration. Methods Following sciatic nerve transection and repair, C57BL/6 J mice were treated for 2 weeks, either with R13, a prodrug that releases the small molecule TrkB ligand, 7,8-dihydroxyflavone, with compound 11 (CP11), an inhibitor of asparaginyl endopeptidase (δ-secretase), or with a control vehicle. Four weeks after injury, different fluorescent retrograde tracers were injected into the gastrocnemius and tibialis anterior muscles to mark DRG neurons that had successfully reinnervated these muscles. Using immunofluorescence, retrogradely labeled DRG neurons also expressing markers of four different sensory neuronal classes were counted. Results and discussion Treatments with R13 or CP11 resulted in muscle reinnervation by many more DRG neurons than vehicletreated controls, but neurons expressing proteins associated with the different classes of DRG neurons studied were largely in the same proportions found in intact mice.